2000
DOI: 10.3141/1701-15
|View full text |Cite
|
Sign up to set email alerts
|

Summary of Design Speed, Operating Speed, and Design Consistency Issues

Abstract: Six papers in this Record were presented at a conference session during the January 1994 TRB annual meeting. They address various aspects of the relationships among design speed, operating speed, and design consistency. All six papers are examined to show the interrelationships of design speed, operating speed, and design consistency; what changes are needed in the current design process and current design policies; how the concept of design consistency can produce better designs; and what research is needed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They suggested that the difference between design and operating speeds should not exceed 15 kph. The difference between the operating speed for passenger cars and heavy vehicles should be limited to the same threshold.Harwood, Neuman and Leisch (2000) suggested the following loop for determining design speeds:1. The designer selects a design speed.…”
mentioning
confidence: 99%
“…They suggested that the difference between design and operating speeds should not exceed 15 kph. The difference between the operating speed for passenger cars and heavy vehicles should be limited to the same threshold.Harwood, Neuman and Leisch (2000) suggested the following loop for determining design speeds:1. The designer selects a design speed.…”
mentioning
confidence: 99%